PELATIHAN PENYUSUNAN SILABUS PENGAJARAN BAHASA INGGRIS BAGI GURU-GURU BAHASA INGGRIS DI TITIP SENTANI, KABUPATEN JAYAPURA - Izak Morin; Wigati Yektiningtyas; Precilia Rafra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstrak Training Indonesians for Transition to Institutional Programs (TITIP) is one of the priority programs of the Yayasan Pelayanan Antarbudaya Papua (YPA-Papua). This foundation is a nonprofit social organization founded in 1992 and based in Sentani, Jayapura Regency, Papua Province. English is one of the subjects within the TITIP curriculum.According to a survey conducted by the Head of the Community Service Team (PkM) from the English Education Study Program, FKIP Uncen, during discussions with one of the leaders of YPA-Papua, it was found that most of the English teachers recruited to teach this subject lack formal teaching qualifications. They often rely on their command of the English language, teaching based on the knowledge and experience they have acquired. This situation has become a concern for YPA-Papua, prompting the PkM FKIP Uncen Team to offer expert assistance in the form of training for TITIP English teachers to address this issue. One of the activities proposed is the